2023
DOI: 10.1002/admt.202202065
|View full text |Cite
|
Sign up to set email alerts
|

Highly Sensitive, Ultrawide Range, and Multimodal Flexible Pressure Sensor with Hierarchical Microstructure Prepared By a One‐Step Laser Printing Process

Abstract: The hierarchical microstructures composed of surface microstructures and porous structures on soft materials have attracted more and more attention because of their effectiveness in improving flexible sensor performance. However, the preparation methods of the hierarchical microstructures are faced with the problems induced by complex process, high cost, and low efficiency. Up to now, there is no one-step method that can directly realize the hierarchical microstructure on soft materials, even polydimethylsilox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Due to the controllable preparation of the hollow graphene microspheres, the variation in the relative current versus pressure curves from device to device is negligible (Figure S15). Moreover, a comparison of the pressure-sensing performance between the as-prepared HGP-film-based sensor and the research of other common micropattern-based sensors is shown in Figure h, demonstrating that this work achieves a superior sensitivity for a wide linear range. ,,, …”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…Due to the controllable preparation of the hollow graphene microspheres, the variation in the relative current versus pressure curves from device to device is negligible (Figure S15). Moreover, a comparison of the pressure-sensing performance between the as-prepared HGP-film-based sensor and the research of other common micropattern-based sensors is shown in Figure h, demonstrating that this work achieves a superior sensitivity for a wide linear range. ,,, …”
Section: Resultsmentioning
confidence: 84%
“…In addition to surface micropatterned structures, introducing a porous active layer can also decrease the modulus of the materials and permit more three-dimensional microstructure design of the active layer. Generally, the pore size and pore shape introduced through chemical foaming and natural mold are not controllable and tunable, and the regular porous structure prepared through the hard template often contains complicated processes and toxic reagents. , Notably, both the micropatterned surface and the hybrid porous microstructure play important roles in improving the sensing performance. The common way of combining multiple microstructures by introducing a micropatterned surface on the internal porous material helps to further achieve high-performance sensors. , For example, Zhao fabricated a pressure sensor based on a hybrid structure through a one-step microwave irradiation process, showing a high sensitivity of 611.85 kPa –1 . Therefore, developing a facile and low-cost method to achieve random surface patterns and tunable porous bulk structure design, which shows great potential in synergistically optimizing the performance of the sensors, is of great potential.…”
Section: Introductionmentioning
confidence: 99%
“…Especially, the pressures generated by human motion, such as grip pressure, , plantar pressure, and joint bending pressure, are of particular interest to flexible pressure sensors for health monitoring and healthcare applications. These pressures are predominantly distributed in a medium-pressure regime (10–100 kPa). , However, at present, the pressure sensors with high sensitivity are normally restricted into a narrow pressure range of detection (ROD) lower than 10 kPa, while those with a wide ROD over 100 kPa generally have low sensitivity. For example, the flexible pressure sensor based on a microstructured porous pyramid possesses a sensitivity of as high as 449 kPa –1 but only within the pressure range of 0.14–10 Pa . On the contrary, the sensor based on a porous sponge can respond through an ultrawide pressure sensing range from 10 Pa up to 1.2 MPa but exhibits sensitivity of only 0.01–0.02 kPa –1 .…”
Section: Introductionmentioning
confidence: 99%
“…With the need for booming developments in the fields of flexible wearable devices, smart healthcare, human–computer interaction, electronic skin, and smart electro-textiles (e-textiles), , persistent studies on flexible electronic devices , have become more urgent and indispensable. Flexible electronic devices are flexible, thin low-cost, and have adjustable mechanical properties.…”
Section: Introductionmentioning
confidence: 99%